Exploitation of Castor Genotypes for Enhanced Eri Silk Production and the Prospects for its Promotion among the Farming Community - Narayanamma, V. Lakshmi; Ratnakar, V.; Shiva, B.; Vishwatej, R.; Prasad, M. Ram; Rajasri, M. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at the research farm of Regional Agricultural Research Station (RARS), Palem, Telangana State, India during rabi (October–January) seasons of 2012–13 and 2013–14 to exploit the high yielding castor genotypes with respect to scientific ericulture and to know the prospects for its rate of adoption. Amid the eight genotypes of castor, highest 10th day larval weight of 0.645 g, 0.651 g and 0.639 and highest mature larval weight of 6.012 g, 5.982 and 5.948 g was recorded in the eri silkworm reared on PCH-111, PCH-222 and GCH-4 respectively. Enhancement in shell weight (0.981 g) was obtained in the eri silkworm fed on PCH-111 followed by GCH-4 (0.778 g). Significantly highest ERR was recorded in the eri silkworm reared on PCH-111 (92.7%) genotype and PCH-222 (92.23%) with no significant difference among them. The mortality rate of the eri silkworms reared on different castor genotypes ranged between 3.3%–12.08%. Significantly the highest survival rate of 96.15% was recorded in the eri silkworms reared on Haritha genotype followed by PCH-222 (94.06%). The study revealed that nearly 61.25% of the eri rearers exhibited medium level of extent of adoption, followed by 21.25% with low level of extent of adoption, while about 17.50% of the rearers exhibited high adoption respectively with respect to scientific method of ericulture practices. The perusal of the data revealed that out of nine dependent variables, six variables viz, age, educational qualification, size of land holding, family annual income, risk bearing of the rearers and knowledge gained through training were positively and significantly related with the extent of adoption.